Incidencia y severidad de la muerte regresiva en Persea americana, var. Hass sobre Porta - Injertos Zutano, Lula o Topa - Topa. Virú - La Libertad - Sandoval Bardales, Eduardo Arturo (2019)
Lasiodiplodia theobromae is a phytopathogenic fungus that severely affects the cultivation of avocado in any state of development, causing infections in the area of pattern-graft insertion of young plants, "descending death" of branches, formation of chancros and necrosis of the peduncle of fruits . The objective of the present investigation was to study the incidence and severity of the disease known as regressive death of the avocado. For this, production fields of avocado var. Hass grafted on the Zutano, Lula and Topa Topa patterns, located in the Virú province of Virú district in La Libertad. Three batches of 2.28 ha were evaluated for each graft holder, the sampling unit was 10% of the population (105 plants per batch). The incidence was determined by recording the presence or not of the disease and for the severity a descriptive scale of the symptoms of the disease was used based on degrees. The incidence and severity of regressive death in Persea americana var. Hass with the Zutano graft holder was 56.19% and 14.29% respectively, in the plants with the Lula rootstock of 64.13% 17.46% and in the plants with the Topa-Topa rootstock of 68.89% and 22.30%, being the rootstock that presented the highest incidence and severity percentages, becoming the graft holder most susceptible to regressive death in the Virú locality in Virú, La Libertad.